Across the Dimensions: A Three‐Component Self‐Assembly of Pentaphosphaferrocene‐based Coordination Polymers. Issue 22 (13th March 2023) - Grill, Kevin; Dinauer, Sabrina B.; Peresypkina, Eugenia; Virovets, Alexander V.; Scheer, Manfred
Abstract: Pentaphosphaferrocenes [Cp R Fe(η 5 ‐P5 )] (Cp*=η 5 ‐C5 Me5 ) (A ), Cp''=η 5 ‐C5 H3 tBu2 ‐1, 3 (B )) are excellent building blocks for polymeric assemblies in supramolecular chemistry in combination with coinage metal salts of weakly coordinating anions such as AgSbF6 . Adding rigid aromatic dinitriles ortho/meta/para ‐(NC)2 C6 H4 in a one‐pot reaction between [Cp R Fe(η 5 ‐P5 )] and AgSbF6 leads to various coordination polymers (CPs) by a three‐component self‐assembly. The sterical demand of the differently substituted cyclopentadiene ligands as well as the rigid constitution of the isomeric dinitriles (NC)2 C6 H4 play a key role in the formation of the isolated CPs. All CPs were characterized by NMR spectroscopy, mass spectrometry, elemental analysis, and single‐crystal X‐ray diffraction. Abstract : Coordination polymers : The combination of the rigid, aromatic dinitrile isomers ortho / meta / para ‐(NC)2 C6 H4, the pentaphosphaferrocenes [Cp R Fe(η 5 ‐P5 )] (Cp R =Cp*, Cp''; Cp*=η 5 ‐C5 Me5 ; Cp''= η 5 ‐ C5 H3 tBu2 ‐ 1, 3 ) with different steric demands and a silver salt with a non‐coordinating anion SbF6 − gives a unique view into how those building blocks can influence a three‐component self‐assembly system giving rise to various 1D/2D/3D‐coordination polymers.